FORMING THE TECHNOLOGICAL CONTENT OF THE TEACHER'S INFORMATION-COMMUNICATION COMPETENCE - Tolametov Abdujalil Abdujaparovich (European Science Publishing, 2024)
The article describes what education and information technologies, teacher's IKT-competence, digital and computer literacy, and the effectiveness of their use in organizing the educational process consist of.
Keywords: information technologies, teacher's ICT competence, computer telecommunications, quality of education, digital literacy, computer literacy.